LEUCOCYTE PROFILE OF DETECTION DOGS AT THE STATE POLICE OF THE REPUBLIC OF INDONESIA MALANG CITY POLICE RESOR - Pranadinata, I Gede Galyes; Widyastuti, Sri Kayati; Kendran, Anak Agung Sagung (Buletin Veteriner Udayana, 2023)
Detection dog is one of the animals that assists the task of the Indonesian National Police in maintaining and securing the order of the Indonesian state. Many tasks were given to detection dogs, namely to find explosives, drug-tracking operations, security operations and look for casualities of natural disasters such as landslides and earthquakes. Due to their work environment that are quite extreme and stressful, it affects the stress level of the dog itself, because their working environment greatly affect the hematologic profiles of the dog. Therefore, routine blood examinations are needed such as leucocyte profiling. This study aims to determine the leukocyte profile of detection dog. This research uses descriptive observational research method. The object used in this study is the entire population of Malang City Police's detection dogs. Blood samples were taken and then examined using a hematology analyzer and the blood smears were examined under a microscope using the Diff quik stain. The data obtained were then compared with the hematological standard results, and then analyzed. The results indicate that one of ten samples has leucocytosis and as for differential leukocyte results, the results are quite diverse. Out of ten samples, one sample are found to be limphocytosis, four samples  are found to be lymphositopenia, two samples are found to be monocytosis, one sample are found to be neutrophilia, six samples are found to be eosinophilia and the ten samples for basophils were in the normal range. It is necessary to do advanced sample examination to diagnose the cause of abnormal leukocyte total and leukocyte differential values ??in detection dogs at the State Police of the Republic of Indonesia, Malang City Resor.